Daphnetin: A bioactive natural coumarin with diverse therapeutic potentials - Javed, Maira; Saleem, Ammara; Xaveria, Anne; Akhtar, Muhammad Furqan (Frontiers in Pharmacology, 2022)
Daphnetin (DAP), a coumarin derivative extracted from Daphne species, is biologically active phytochemical with copious bioactivities including anti-inflammatory, anti-oxidant, neuroprotective, analgesic, anti-pyretic, anti-malarial, anti-bacterial, anti-arthritic, neuroprotective, hepatoprotective, nephroprotective, and anti-cancer activities. A wide range of studies have been conducted exploring the significance and therapeutic potential of DAP. This study reviewed various databases such as NCBI, PubMed, Web of Science, Scopus and Google Scholar for published research articles regarding the sources, synthesis, and various bioactivities of DAP using different key words, including but not limited to “pharmacological activities,” “sources,” “neuroprotective effect,” “synthesis,” “cancer,” “anti-inflammatory effect” of “daphnetin.” Furthermore, this review encompasses both in-vivo and in-vitro studies on DAP for treating various diseases. A comprehensive review of the literature revealed that the DAP had a promising pharmacological and safety profile, and could be employed as a pharmaceutical moiety to treat a variety of illnesses including microbial infections, cancer, arthritis, hepatic damage, inflammation and neurological anomalies. The current review intends to provide an in-depth focus on all pharmacological activities and therapeutic approaches for the pharmaceutical and biomedical researchers.